Present at the creation : my life in the NFL and the rise of America's game - Bell, Upton; Borges, Ron (University of Nebraska Press, 2017)
"To understand how the NFL became the sports phenomenon it is today, you can study its history as an active participant. Upton Bell grew up at the knee of the NFL's first great commissioner, his father, the legendary Bert Bell, who not only saved the game from financial ruin after World War II but was one of its greatest innovators. Coining the phrase "On any given Sunday," Bert invented the pro football draft and proposed sudden death rules. Present at the Creation details Bell's firsthand experiences, which started as he watched his father draw up the league schedule each year at the kitchen table using dominoes. There he learned the importance of parity, which is a hallmark of the league's success, and also how to create it. Over the past fifty-three years, Bell has been an owner, a general manager, a personnel executive, a scouting director for two Super Bowl teams, a television commentator and analyst, and a talk-radio host. He has seen the NFL from the inside and has experienced many of the most important moments in NFL history." --